Structural Model Comparison of the Relationship Between Early Maladaptive Schemas and Self-Compassion via Affective Flexibility in Women Seeking Divorce and Non-clinical Women - Arvin, Samaneh; Jahangiri, Mohammad Mehdi; Zangeneh Motlagh, Firoozeh (Psychology of Woman Journal, 2026)
Objective: This study aimed to compare the structural relationships between early maladaptive schemas and self-compassion, mediated by affective flexibility, in women seeking divorce and non-clinical (community) women.Methods and Materials: The research employed a correlational design using structural equation modeling (SEM). The statistical population consisted of all women seeking divorce and non-clinical women who attended counseling and psychology centers in Tehran in 2024. A total of 400 participants (200 women seeking divorce and 200 non-clinical women) were selected using multistage cluster sampling. Participants completed the Self-Compassion Scale (Neff, 2003), Young Schema Questionnaire–Short Form (YSQ-S3; Young, 1998), and the Affective Flexibility Scale (Fu et al., 2018). Data were analyzed using SPSS-26 and AMOS-24 through confirmatory factor analysis and multigroup SEM to assess model fit, path coefficients, and mediation effects via bootstrapping.Findings: The proposed structural model showed good fit indices for both groups. Early maladaptive schemas significantly and negatively predicted affective flexibility (β = −0.211, p < .001) and self-compassion (β = −0.142, p = .048) among women seeking divorce, and also demonstrated negative effects in the community group. Affective flexibility positively predicted self-compassion in both groups (divorce-seeking: β = 0.372, p < .001; community: β = 0.501, p < .001). Bootstrapping results confirmed the mediating role of affective flexibility in the relationship between early maladaptive schemas and self-compassion, with stronger indirect effects observed in the divorce-seeking group (β = −0.0777, p = .006). Multigroup comparisons showed that path differences were significant for Disconnection & Rejection → Affective Flexibility and Impaired Autonomy & Performance → Self-Compassion.Conclusion: Enhancing affective flexibility may therefore strengthen self-compassion and mitigate schema-driven emotional vulnerability in relational distress contexts.